Give and Receive Silence (2018)
This paper is the result of a reflection on the role of silence in the research that, as an artist, has led me to listening to rivers, oceans, and water bodies in sound territories of social-environmental conflict in Colombia. In this paper, silences appear as a political posture of listening that determines the relationships with the body and the landscape, as an anthropic expression of the crisis of water landscapes and, at the same time, as sensitive and resonant material in the creation of a project that finds, in silence, poetic ways of working in the construction of the memories of a dry river. To listen again to the water from the amplified powers of the sonorous, tactile, vibrating body is the possibility of cleaning from them the instrumental representations that reduce it to a matter-object; it is allowing the interpretation of their messages and the opportunity of rhyming in new times of water.